Coexistence in future optical access networks from an operator’s perspective [Invited] - Saliou, Fabienne; Simon, Gael; Le Huerou, Stephane; Chanclou, Philippe; Potet, Jeremy; Gaillard, Georges; Percevault, Ugo; Chevalier, Dylan; Zandueta, Joseph; Yang, Bo; Vagionas, Christos; Gatzianas, Marios; et al. (Journal of optical communications and networking, 2024)
In this paper, we address the challenges related to the simultaneous operation of legacy and future network technologies in passive optical networks (PONs) and point-to-point topologies. We explore the coexistence issues for various user categories, including residential, enterprise, factories, and mobile users. The future access networks will need to accommodate multiple technologies concurrently. Our paper demonstrates how G-PON, XGS-PON, and 50G-PON can coexist on the same optical distribution network using triple coexistence multi-PON modules. However, there are certain limitations that need to be considered, such as achieving a high optical budget and the associated costs, both in terms of monetary investment and {{\rm CO}_2} emissions for technology deployment by operators. Additionally, we emphasize the significance of optical line terminals (OLTs) as crucial network components in the future. OLTs play a central role in supporting the traffic evolution with optimal efficiency in terms of throughput, latency, jitter, and adherence to {{\rm CO}_2} emission constraints. Finally, we experimentally demonstrate the first assessment, to our knowledge, of a 50G-PON prototype with optical budget reaching 23.9 dB limited by the downstream (DS). Furthermore, we evaluate the potential limitations regarding coexistence by examining the effects of stimulated Raman scattering between the DS of 50G-PON and the upstream of XGS-PON for the first time with real PON systems.